Are You Ready for More Insulin Concentrations? - Segal, Alissa R. (J Diabetes Sci Technol, 2014)
Practitioners need to prepare for a rapid expansion of new concentrated insulins. For many years, the treatment regimens for patients have been limited to 2 concentrations (100 units/mL and 500 units/mL), which pose challenges to both patients and providers. As the new concentrated insulins are at various stages of development, this manuscript reviews the available information on the new concentrated products. This information was obtained from publications, poster presentations, abstracts, and the manufacturers for the products in earlier stages of development. To have a basis for comparison, it is important to understand the activity profile and the challenges with use of the currently available concentrated insulin, regular insulin 500 units/mL (U500R). We also examine how the newer products may assist clinicians and patients with the difficulties faced with the use of U500R.